BiOX/Bi/BiOX (X = Cl, Br) Double‐Side Nanosheet Arrays: Synthesis, Structures, and Photo(electro)catalytic Applications. Issue 19 (28th May 2022) - Li, Wenjuan; Wang, Xue; Zhang, Yipin; Zhu, Shuao; Zhao, Mengjun; Zhang, Hongwen; Wang, Yujie; Zhang, Dapeng; Ran, Weiguang; Zhang, Lulu; Li, Na; Yan, Tingjiang
Abstract: Array‐structured photocatalysts, featuring unique transport properties of charge carriers and special texture structures, have captured widespread interest in photocatalytic and/or photoelectrocatalytic applications. However, the fabrication of arrays usually suffers from complicated synthetic routes and the indispensable use of substrates. Herein, a novel BiOX/Bi/BiOX (X = Cl, Br) double‐side nanosheet array catalyst, with vertically aligned BiOX nanosheets symmetrically grown on the two sides of horizontal Bi nanoplates, is first constructed by a facile solution‐phase solvothermal route in the absence of any substrates. Both l ‐cysteine and ethylene glycol are found to play critical roles in the formation of Bi nanoplates and the growth of BiOX nanosheets. Thanks to the synergism of double‐side metal‐semiconductor array, BiOX/Bi/BiOX presents significantly boosted performance for photocatalytic selective oxidation of benzyl alcohol to benzaldehyde, far surpassing Bi/BiOX and pristine BiOX. Additionally, BiOX/Bi/BiOX also exhibits superior photoelectrocatalytic performance with excellent hydrogen and oxygen evolution reaction activity. The electrochemical analysis and photoluminescence results reveal that the middle Bi nanoplate can function as a fast transport channel for photogenerated electrons, significantly accelerating the separation of photogenerated carriers. This work provides a general substrate‐free strategy to construct array catalysts with double‐side structure and reveals the outstanding advantages toward improved photocatalysis. Abstract : BiOX/Bi/BiOX (X = Cl, Br) double‐side nanosheet array catalyst, with vertically aligned BiOX nanosheets symmetrically grown on the two sides of horizontal Bi nanoplates, is constructed by a facile solvothermal route in the absence of any substrates. It shows enhanced photo(electro)catalytic performance in the selective oxidation of PhCH2 OH to PhCHO and hydrogen and oxygen evolution.